Preparation of pH indicator electrode based on modified ternary materials of lithium-ion batteries and method thereof

Through the modified lithium -ion battery three yuan material to prepare a full solid -state pH indicator electrode, the problem of resistance, stability and drift of traditional sensors in marine pH monitoring, and realized the far -reaching sea monitoring of high response accuracy and corrosion resistance.

CN118777392BActive Publication Date: 2025-01-24OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410972413.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-01-24
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

The prior art is difficult to achieve long-term, in-situ and real-time monitoring of ocean pH, especially in deep ocean environments, where traditional sensors have pressure resistance, stability and drift problems.

Method used

By modifying the lithium-ion battery ternary material (NCM or NCA) and using steps such as acid impregnation, electrochemical reduction, and buffer solution immersion, an all-solid-state pH indicating electrode is prepared. The electrode uses the NiOOH/Ni(OH)2 redox couple as the main pH-responsive active layer and contains cobalt and manganese oxides, which improves stability and corrosion resistance.

Benefits of technology

The high response accuracy, voltage resistance, corrosion resistance and pollution -resistant loss of all -solid -state PH indicating electrodes are suitable, and it is suitable for long -term, original and real -time monitoring of seawater pH values.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118777392B_ABST
    Figure CN118777392B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a pH indicator electrode based on the modification of lithium-ion battery ternary materials, and selects commercial and inexpensive lithium-ion battery ternary electrode materials (lithium nickel cobalt manganese oxide / NCM or lithium nickel cobalt aluminum oxide / NCA), or even discarded NCM or NCA, as active substances, and obtains an all-solid-state pH indicator electrode with excellent performance after a series of modification and stabilization treatments, in order to solve the problem of long-term, in-situ monitoring of ocean pH. Through the technical solution of the present invention, the all-solid-state pH indicator electrode of the present invention and its preparation method have the advantages of simple manufacturing, low cost, good pH response characteristics, high response accuracy, strong pressure resistance, corrosion resistance and anti-fouling performance, and small potential drift, and are particularly suitable for long-term, in-situ and real-time monitoring of seawater pH in the deep sea.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical sensors, and in particular to a method for preparing a pH indicating electrode based on modified ternary materials of a lithium ion battery. Background Art

[0002] pH value is one of the important parameters of seawater and is a sign of the acidity and alkalinity of seawater. Marine scientific research requires a large number of accurate parameters about the pH value of seawater. These parameters are of great significance to human understanding, research and utilization of the ocean. For example, the measured pH value of seawater and other parameters of seawater can be combined to calculate the content of CO2 in seawater, which provides accurate data for people to study ocean acidification; and can help people understand the living environment of different marine animals and plants, so as to better understand their growth and reproduction laws; in addition, the existence form of various elements in seawater and the chemical reaction process in the ocean are also directly affected by the pH value of seawater. Therefore, many fields rely on the accurate measurement, monitoring and recording of the pH value of seawater, and real-time monitoring of the pH value of seawater is an urgent need in these fields. At present, the pH value of the ocean has been insufficiently sampled in space and time for a long time. The fundamental reason is that most oceans are located in remote areas, the environment is harsh, and in-situ measurements are difficult. Most pH measurements are carried out in laboratories on ships after sampling. However, laboratory sampling and measurement have problems such as difficulty in knowing the real-time pH value of seawater and deterioration of seawater during storage.

[0003] The field of marine pH monitoring has long relied on optical sensors, potentiometric sensors, and sampling measurements; in-situ measurements have placed higher demands on the pressure resistance and stability of sensors. The sophisticated and complex internal structure of optical sensors is not suitable for use in harsh working conditions and high-pressure seawater; the most commonly used potentiometric sensors for seawater pH measurement are glass electrodes and metal oxide electrodes. Due to the fragility and easy drift of glass electrodes, their application in the field of in-situ measurements is limited to installation in pressure-resistant containers and short-term measurements on submersibles; and metal oxide pH indicator electrodes have difficult-to-solve drift problems, and long-term monitoring depends on regular calibration. Therefore, the current field of in-situ long-term measurement of seawater pH is still unsatisfactory, and the need to develop a new generation of pH sensors to meet the needs of long-term, in-situ, and real-time monitoring of seawater pH in the deep sea is a key issue that needs to be urgently addressed. Summary of the invention

[0004] In order to make up for the shortcomings of the prior art, the present invention provides a method for preparing a pH indicator electrode based on the modification of lithium-ion battery ternary materials. Commercial and inexpensive lithium-ion battery ternary electrode materials (lithium nickel cobalt manganese oxide / NCM or lithium nickel cobalt aluminum oxide / NCA), or even discarded NCM or NCA, are selected as active materials, and a full-solid-state pH indicator electrode with excellent performance is obtained after a series of modification and stabilization treatments, in order to solve the problem of long-term, in-situ monitoring of ocean pH.

[0005] The present invention is achieved through the following technical solution: a method for preparing a pH indicator electrode based on the modification of a lithium ion battery ternary material, specifically comprising the following steps:

[0006] (1) Acid immersion treatment process: NCM or NCA, a lithium-ion battery ternary material, or a Ti-based NCM or NCA composite electrode is first made and immersed in a sulfuric acid aqueous solution. After 1-7 days, it is taken out, washed with water until neutral, and dried for subsequent processes;

[0007] (2) Composite electrode preparation process: NCM or NCA, or NCM or NCA after acid leaching, a mixed slurry or mixed powder of a conductive agent and a binder is rolled onto a current collector Ti mesh to form a Ti-based NCM or NCA composite electrode;

[0008] (3) Electrochemical reduction process: The acid-impregnated Ti-based NCM or NCA composite electrode is electrochemically reduced in a sodium chloride solution at a constant potential of 0.0-0.3 V relative to a saturated calomel electrode (SCE) for 1-24 h to obtain a reduced Ti-based NCM or NCA composite electrode for subsequent processes;

[0009] (4) The reduced Ti-based NCM or NCA composite electrode is immersed in a buffer solution with a pH range of 7-12 for 1-15 days to finally obtain a fully solid-state pH indicating electrode composed of a NiOOH / Ni(OH)2 redox couple as the main pH-responsive active layer and cobalt and / or manganese oxides that play a stabilizing role, which together with a conductive agent and a binder form an electrode.

[0010] As a preferred embodiment, the Ti-based NCM or NCA composite electrode, wherein the mass ratio of NCM or NCA, or NCM or NCA after acid leaching, to the conductive agent and the binder is in the range of (80-96)%: (1-5)%: (3-15)%.

[0011] As a preferred embodiment, the wet process technology is to disperse or dissolve the powders of NCM or NCA, conductive agent and binder in N-methylpyrrolidone (NMP) to form a slurry, and then roll it onto the current collector Ti mesh, and obtain a Ti-based NCM or NCA composite electrode after drying; the dry process technology is to directly mix the powders of NCM or NCA, conductive agent and binder through high shear force to form a uniform mixed powder, and then roll it onto the current collector Ti mesh to directly obtain a Ti-based NCM or NCA composite electrode.

[0012] As a preferred solution, NCM (LiNi x Co y Mn 1-x-y O2) According to the group distribution ratio x:y:(1-xy), they are NCM111, NCM523, NCM622 and NCM811, and NCA is LiNi 0.8 Co 0.15 Al 0.05 O2, or waste recycled NCM or NCA; the conductive agent is one or more of nano conductive carbon black, carbon tube and graphene; the binder is one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) emulsion and carboxymethyl cellulose (CMC).

[0013] As a preferred embodiment, the oxides are cobalt and / or manganese, wherein the cobalt oxide is CoO and / or Co3O4, and the manganese oxide is MnO and / or Mn3O4.

[0014] As a preferred embodiment, after the acid immersion treatment, the concentration of the aqueous sulfuric acid solution is not less than 0.1 mol / L.

[0015] As a preferred embodiment, the Ti-based NCM or NCA composite electrode made of NCM or NCA after acid leaching, or the Ti-based NCM or NCA composite electrode after acid leaching, the electrode potential of the above composite electrode in sulfuric acid aqueous solution is not less than 1.0 V relative to saturated calomel electrode (SCE), that is, after sulfuric acid immersion treatment, an oxidized Ti-based NCM or NCA composite electrode is obtained.

[0016] As a preferred solution, the film is rolled onto a current collector Ti mesh, wherein the rolling temperature is 100-200° C., and the mesh number and thickness of the Ti mesh are 10-180 meshes and 0.05-0.5 mm, respectively.

[0017] As a preferred solution, the reversible response range of the pH value of the all-solid-state pH indicating electrode is 5-12, and the optimized reversible response range of the pH value without potential drift is 7-9.

[0018] The pH indicating electrode prepared by the preparation method of the present invention is prepared based on the modification of the ternary material of lithium-ion battery. Through wet or dry electrode technology, NCM or NCA, conductive agent and binder mixture are rolled onto the current collector Ti mesh to form a Ti-based NCM or NCA composite electrode. Then, through acid leaching, electrochemical reduction and immersion in a buffer solution, a pH-responsive active layer with NiOOH / Ni(OH)2 redox couple as the main layer and cobalt and manganese oxides that play a stabilizing role are formed on the surface. Together with the conductive agent and the binder, they constitute an all-solid-state pH indicating electrode. Another equivalent technical solution is: firstly treat NCM or NCA with acid to obtain acid-treated NCM or NCA, and then roll the NCM or NCA, conductive agent and binder mixture onto the current collector Ti mesh through wet or dry electrode technology to form a Ti-based NCM or NCA composite electrode, and then through electrochemical reduction and immersion in a buffer solution, a pH-responsive active layer with NiOOH / Ni(OH)2 redox couple as the main component and cobalt and / or manganese oxides that play a stabilizing role are formed on the surface, which together with the conductive agent and binder constitute an all-solid-state pH indicating electrode.

[0019] Due to the adoption of the above technical scheme, the present invention has the following beneficial effects compared with the prior art: the all-solid-state pH indicator electrode and the preparation method thereof of the present invention are simple to manufacture, low in cost, good in pH response characteristics, high in response accuracy, strong in pressure resistance, corrosion resistance and anti-fouling performance, and small in potential drift, and are particularly suitable for long-term, in-situ and real-time monitoring of seawater pH value in the deep sea.

[0020] Additional aspects and advantages of the present invention will become apparent from the following description or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 Schematic diagram of the all-solid-state pH indicating electrode and its preparation method of the present invention;

[0023] Figure 2 This is a scanning electron microscope (SEM) photograph of the surface of the all-solid-state pH indicator electrode;

[0024] Figure 3 (a and b) are X-ray diffraction (XRD) patterns of phase structure changes of the all-solid-state pH indicator electrode during the preparation process;

[0025] Figure 4 It is the E-pH response curve of the all-solid-state pH indicating electrode in the pH range of 5-12;

[0026] Figure 5 It is the reversible E-pH response curve of the all-solid-state pH indicating electrode in pH 7-9 solution;

[0027] Figure 6 The potential-time curve of the all-solid-state pH indicating electrode when the pH value is changed from pH 7 to pH 9 with a change amplitude of 0.5 pH;

[0028] Figure 7 E-pH curves of the solid-state pH indicating electrode after immersion in pH 8 buffer solution for 1 day and 120 days. DETAILED DESCRIPTION

[0029] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0031] Combine the following Figures 1 to 3 The pH indicating electrode and method thereof prepared by modifying the ternary material of a lithium-ion battery according to an embodiment of the present invention are specifically described.

[0032] like Figure 1As shown, the present invention proposes a method for preparing a pH indicator electrode based on the modification of lithium-ion battery ternary materials, (1) acid impregnation treatment process: lithium-ion battery ternary materials NCM or NCA, or Ti-based NCM or NCA composite electrodes are first made and immersed in a sulfuric acid aqueous solution, taken out after 1-7 days, washed with water to neutrality, and dried for subsequent processes; (2) composite electrode preparation process: NCM or NCA, or NCM or NCA after acid immersion treatment, a mixed slurry or mixed powder of a conductive agent and a binder is rolled onto a current collector Ti mesh to form a Ti-based NCM or NCA composite electrode; (3) electrochemical reduction treatment process: the Ti-based NCM or NCA composite electrode after acid immersion treatment is electrochemically reduced to 1-24 V at a constant potential of 0.0-0.3 V relative to a saturated calomel electrode (SCE) in a sodium chloride solution. h, and obtain a reduced Ti-based NCM or NCA composite electrode for subsequent processes; (4) immersing the reduced Ti-based NCM or NCA composite electrode in a buffer solution with a pH range of 7-12 for 1-15 days, and finally obtaining a NiOOH / Ni(OH)2 redox couple as the main pH response active layer, and cobalt and / or manganese oxides that play a stabilizing role, which together with a conductive agent and a binder constitute an all-solid-state pH indicating electrode.

[0033] Example 1

[0034] pH sensitive materials are usually coated on supporting materials to form durable electrodes. The present invention uses Ti mesh as the supporting material for the active material. Through dry electrode technology, NCM 523, multi-walled carbon nanotubes and polytetrafluoroethylene powders are mixed into uniform powders in a mass ratio of 90%:2%:8% by a jet crusher, and then heated to 180°C by a roller press. The powder is rolled onto a 80-mesh Ti mesh with a thickness of 0.2 mm to form a Ti-based NCM 523 composite electrode; then the composite electrode is immersed in 0.5 mol / L H2SO4 for 2 days, and the natural potential reaches 1.05V. vs.‍SCE , an oxidized Ti-based NCM 523 composite electrode was obtained; the oxidized composite electrode was then charged at 250 mV in a 3.5 wt% sodium chloride solution using an electrochemical workstation. vs.‍SCE The reduced Ti-based NCM 523 composite electrode was obtained by constant potential reduction for 12 h. Finally, the reduced composite electrode was placed in a pH 7 buffer solution and stabilized for about 10 days to reach a stable potential, thereby obtaining a pH-responsive active layer with NiOOH / Ni(OH)2 redox couple as the main component, as well as CoO and Co3O4, MnO and Mn3O4 that play a stabilizing role, which together with multi-walled carbon nanotubes and polytetrafluoroethylene constituted an all-solid-state pH indicating electrode.

[0035] The electrode of the present invention was observed by SEM surface morphology. Figure 2 As shown, the material particles are spherical and evenly distributed, and multi-walled carbon nanotubes and filamentous polytetrafluoroethylene shuttle in the gaps of the spherical NCM 523 particles, which improves the overall conductivity and molding stability of the electrode. Since the preparation of the electrode has undergone high-pressure pressing on a roller press, the protruding particles on the surface are flattened, and the gaps between the particles are small and relatively dense; after being soaked in sulfuric acid, due to erosion and overflow of oxygen bubbles, the particles are partially broken, the surface becomes porous, the active surface area increases, and the surface wettability improves; electrochemical reduction does not lead to significant changes in the morphology of the electrode, and mainly changes in the valence states of Ni, Co and Mn elements occur; after long-term immersion in buffer, the arrangement of the crystals becomes more regular.

[0036] Figure 3 (a and b) are XRD diagrams of the phase structure change of the above-mentioned all-solid-state pH indicator electrode during the preparation process. It can be seen that the original electrode is a layered structure (R-3m space group), which is consistent with LiNiO2. The 108 / 110 peak of the electrode after acid leaching basically disappears, and the layered structure is transformed into a spinel-like structure (Fd-3m space group). After reduction, the electrode is transformed into a rock salt phase (Fm-3m space group), which corresponds to the three diffraction peaks of 37.6°, 43.69°, and 63.51° in the standard card PDF#74-2257; in addition, after stabilization in the buffer solution, the intensity of each diffraction peak is greater, indicating that the degree of crystallization of the rock salt phase structure is higher after long-term immersion in the solution. In summary, during the electrode processing, the structure of the NCM 523 material undergoes a transformation from layered-disordered spinel structure to rock salt phase.

[0037] The above all-solid-state pH indicator electrode was used as the working electrode, and the pH was transferred from pH 7 to pH 9 buffer at intervals of 0.5 pH, and then from pH 9 buffer to pH 7 step by step, and its open circuit potential was recorded to obtain Figure 5 , compare the open circuit potential difference of the electrodes at the same pH to evaluate the reversibility of the pH electrode. From the figure, it can be seen that the potential difference of the working electrode corresponding to the same pH is 1.22mV ~ 4.53mV. The electrode shows good reversibility and small hysteresis potential in the test.

[0038] The all-solid-state pH indicator electrode was used as the working electrode, immersed in a buffer solution of pH 7 and waited for the potential to stabilize, then the pH was gradually increased by 0.5 pH value each time and waited for the potential to stabilize until pH 9 was reached. The potential-time curves of ΔpH0.5 in buffer solutions of different pH values ​​were obtained as shown in Fig. Figure 6 As can be seen from the figure, the potential remains almost unchanged after stabilization at each pH (12 h), showing that the pH indicator electrode has good stability; the response time (t 90) are different, corresponding to the response time (t 90 ) are 1.98 h, 1.67 h, 1.17 h, and 0.92 h, respectively. Compared with the traditional glass electrode, the longer pH response time is its disadvantage. However, the long-term, in-situ, and real-time monitoring of seawater pH in the deep sea does not require a high response time, which is particularly suitable for the application of the all-solid-state pH indicator electrode of the present invention. In addition, Figure 7 The E-pH curves of the all-solid-state pH indicator electrode at the 1st day and the 120th day after being immersed in a pH 8 buffer solution are shown. The two curves basically overlap, indicating that the pH indicator electrode has excellent long-term stability and solves the drift problem of traditional solid-state pH indicator electrodes.

[0039] Example 2

[0040] NCM 811 was soaked in 2 mol / L H2SO4 sulfuric acid aqueous solution, and after stirring for 7 days, the concentration of the sulfuric acid aqueous solution was reduced to 0.3 mol / L, taken out, washed with water to neutrality, and dried for subsequent processes. Through wet electrode technology, the acid-leached NCM 811, conductive carbon black and polyvinylidene fluoride (PVDF) powder were dispersed in N-methylpyrrolidone (NMP) solvent according to a mass ratio of 84%: 4%: 12%, and stirred at high speed to obtain a slurry. After heating to 160°C by a roller press, the slurry was coated and rolled onto a 180-mesh Ti mesh with a thickness of 0.05 mm to obtain a Ti-based NCM 811 composite electrode, and an oxidized Ti-based NCM 811 composite electrode was obtained at the same time; the oxidized composite electrode was then placed in a 0.5 mol / L sodium chloride solution using an electrochemical workstation at 50 mV vs.‍SCE After constant potential reduction for 24 h, a reduced Ti-based NCM 811 composite electrode was obtained; finally, the reduced composite electrode was placed in a pH 9 buffer solution and stabilized for about 15 days to reach a stable potential, thereby obtaining a pH-responsive active layer with NiOOH / Ni(OH)2 redox couple as the main component, and Co3O4 and Mn3O4 that play a stabilizing role, which together with conductive carbon black and polyvinylidene fluoride constituted an all-solid-state pH indicator electrode.

[0041] Example 3

[0042] NCA was soaked in a 2 mol / L H2SO4 sulfuric acid aqueous solution, and after stirring for 3 days, the concentration of the sulfuric acid aqueous solution was reduced to 1 mol / L, taken out, washed with water until neutral, and dried for subsequent processes. By wet electrode technology, the acid-leached NCA, single-walled carbon nanotubes, reduced graphene oxide and polyacrylic acid (PAA) powders were dispersed in N-methylpyrrolidone (NMP) solvent in a mass ratio of 80%: 4%: 1%: 15%, and stirred at high speed to obtain a slurry. After heating to 190°C by a roller press, the slurry was coated and rolled onto a 120-mesh Ti mesh with a thickness of 0.1 mm to obtain a Ti-based NCA composite electrode, and an oxidized Ti-based NCA composite electrode was obtained at the same time; the oxidized composite electrode was then placed in a 0.6 mol / L sodium chloride solution using an electrochemical workstation at 150 mV vs.‍SCE The reduced Ti-based NCA composite electrode was obtained by constant potential reduction for 6 h. Finally, the reduced composite electrode was placed in a pH 8 buffer solution and stabilized for about 5 days to reach a stable potential, thereby obtaining a pH-responsive active layer with NiOOH / Ni(OH)2 redox couple as the main component, and CoO and Co3O4 that play a stabilizing role. Together with single-walled carbon nanotubes, reduced graphene oxide and polyvinylidene fluoride, they constituted an all-solid-state pH indicating electrode.

[0043] The all-solid-state pH indicator electrode obtained by the preparation method of the present invention can be applied to pH monitoring of neutral and alkaline environmental media, and is particularly suitable for long-term, in-situ and real-time monitoring of seawater pH changes in the deep sea.

[0044] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0045] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a pH indicator electrode based on modified lithium ion battery ternary materials, characterized in that: The specific steps include: (1) Acid immersion treatment process: NCM or NCA, a lithium-ion battery ternary material, or a Ti-based NCM or Ti-based NCA composite electrode is first made and then immersed in a sulfuric acid aqueous solution. After 1-7 days, it is taken out, washed with water until neutral, and dried for subsequent processes. (2) Composite electrode preparation process: NCM or NCA, or NCM or NCA after acid leaching, a mixed slurry or mixed powder of a conductive agent and a binder is rolled onto a current collector Ti mesh to form a Ti-based NCM or Ti-based NCA composite electrode; (3) Electrochemical reduction process: The acid-impregnated Ti-based NCM or Ti-based NCA composite electrode is electrochemically reduced in a sodium chloride solution at a constant potential of 0.0-0.3 V relative to a saturated calomel electrode (SCE) for 1-24 h to obtain a reduced Ti-based NCM or Ti-based NCA composite electrode for subsequent processes; (4) Immersing the reduced Ti-based NCM or Ti-based NCA composite electrode in a buffer solution with a pH range of 7-12 for 1-15 days, finally obtaining an all-solid-state indicator electrode with a NiOOH / Ni(OH)2 redox couple as the main pH response active layer, and an all-solid-state pH indicator electrode composed of a NiOOH / Ni(OH)2 redox couple, cobalt and / or manganese oxides that play a stabilizing role, a conductive agent, and a binder.

2. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The Ti-based NCM or Ti-based NCA composite electrode, wherein the mass ratio of NCM or NCA, or NCM or NCA after acid leaching, to the conductive agent and the binder is in the range of (80-96)%: (1-5)%: (3-15)%.

3. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The wet electrode technology is to disperse or dissolve the powders of NCM or NCA, conductive agent and binder in N-methylpyrrolidone (NMP) to form a slurry, and then roll it onto the current collector Ti mesh, and obtain a Ti-based NCM or Ti-based NCA composite electrode after drying; the dry electrode technology is to directly mix the powders of NCM or NCA, conductive agent and binder through high shear force to form a uniform mixed powder, and then roll it onto the current collector Ti mesh to directly obtain a Ti-based NCM or Ti-based NCA composite electrode.

4. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The NCM (LiNi x Co y Mn 1-x-y O2) According to the group distribution ratio x:y:(1-xy), it is NCM111, NCM523, NCM622 or NCM811, and NCA is LiNi 0.8 Co 0.15 Al 0.05 O2, or waste recycled NCM or NCA; the conductive agent is one or more of nano conductive carbon black, carbon tube and graphene; the binder is one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) emulsion and carboxymethyl cellulose (CMC).

5. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The cobalt and / or manganese oxides, wherein the cobalt oxide is CoO and / or Co3O4, and the manganese oxide is MnO and / or Mn3O4.

6. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: During the acid immersion treatment, the concentration of the aqueous sulfuric acid solution is not less than 0.1 mol / L after the process is completed.

7. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: After the acid leaching treatment, the Ti-based NCM or Ti-based NCA composite electrode made of NCM or NCA, or the Ti-based NCM or NCA composite electrode is treated with acid leaching, the electrode potential of the composite electrode in a sulfuric acid aqueous solution is not less than 1.0 V relative to a saturated calomel electrode (SCE), that is, after the sulfuric acid leaching treatment, an oxidized Ti-based NCM or NCA composite electrode is obtained.

8. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The rolling is performed on the current collector Ti mesh, wherein the rolling temperature is 100-200° C., and the mesh number and thickness of the Ti mesh are 10-180 meshes and 0.05-0.5 mm, respectively.

9. The method for preparing a pH indicating electrode based on modified lithium ion battery ternary materials according to claim 1, characterized in that: The pH value reversible response range of the all-solid-state pH indicating electrode is 5-12.

10. A pH indicator electrode prepared by modifying ternary materials of lithium-ion batteries, characterized in that: The pH indicating electrode is prepared by the method for preparing a pH indicating electrode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • PH composite electrode with potential drift influence being eliminated and monitoring and detecting system and method

    CN106525930A

  • Preparation method and application of hydrogen ion-responsive interdigital electrode

    CN109781723A